KEKERASAN SIMBOLIK DALAM ILUSI EMANSIPASI RUANG DIGITAL: (Urgensi Literasi Digital, Perubahan Struktural, dan Transformasi Kultural pada Kekerasan Terhadap Perempuan dan Anak) - Nyoman Ayu Sukma Pramestisari (D3 Perpustakaan FISIP UNUD, 2025)
ABSTRACT Digital transformation is often understood as an expansion of the public sphere that is democratic and emancipatory, enabling individuals to participate on equal terms without being constrained by conventional social hierarchies. However, this article advances a sociological critique of this assumption by demonstrating that digital space is not neutral, but rather operates as a social field that reproduces existing power relations and social inequalities. The central focus of this article is to explain how women and children are socially produced as vulnerable groups within digital spaces through mechanisms of symbolic violence that function latently and are socially legitimized. Employing a qualitative approach through a literature-based study, this article examines recent scholarship on online gender-based violence, children’s vulnerability within digital ecosystems, and the interrelations between technology, patriarchal culture, and structures of power. The analysis reveals that the vulnerability of women and children does not stem from biological differences, but from society’s failure to understand gender as a social construction distinct from sex as a biological condition. This conceptual misrecognition leads to the naturalization of subordination, the justification of control over women’s bodies and expressions, and the delegitimization of children’s experiences of violence. Drawing on Pierre Bourdieu’s theoretical framework, digital space is conceptualized as a social field in which symbolic capital is unequally distributed, while patriarchal habitus and gendered doxa shape social acceptance of such inequalities. Symbolic violence operates through language, representation, algorithms, and interactional norms that constrain the agency of subordinate groups without overt coercion. This article argues that digital literacy approaches that focus solely on individual responsibility risk reinforcing symbolic domination. Therefore, a critical sociological perspective is necessary to dismantle the illusion of digital emancipation and to reclaim digital space as an arena of equitable social participation. Keywords: Symbolic violence, Digital space, Gender-based inequality, Women, Children